Empowerment, adaptation, and agricultural production: Evidence from Niger - Wouterse, Fleur (International Food Policy Research Institute, 2017)
Located at the heart of West Africa, Niger is a landlocked country with three-quarters of its territory covered by the Sahara Desert. Niger’s climate is mostly arid, and it is one of the least developed countries in the world. The vast majority of its population lives in rural areas, and the country is strongly dependent on agriculture. Agriculture is predominantly rainfed and yields rely on one rainy season. Although productivity in Niger has shown a positive trend, agriculture has been strongly affected in recent decades by several crises partly or entirely due to extreme weather events. Farmers pursue a number of strategies in the face of climatic (and nonclimatic) stressors including soil and water conservation methods such as barriers, terracing, and planting pits, and their adaptive capacity is deemed critical for estimating the economic impact of climate change. An understanding of climate change adaptation processes at the farm household level is therefore crucial to the development of well-designed and targeted mitigation policies. In this study, we use new data from Niger and regression analysis to study climate change adaptation through the digging of zaї pits and food production and the role of human capital measures therein. We find that adaptation is influenced by the perception that the frequency of droughts has increased and by the availability of financial resources and household labor. Adaptation is also influenced by educational attainment—both formal and Koranic school education. Adaptation of zaї pits is found to play an important role in food productivity. Our counterfactual analysis reveals that even though all households would benefit from adaptation, the effect is found to be significantly larger for households that actually did adapt relative to those that did not, indicating that the prospects of closing the productivity gap through encouraging adaptation in less well-endowed households are limited.